Nature of the Environment for the Forestry Sector in India - Gupta, Tirath R. (Indian Forester, 1978)
The paper has analysed the impact of the economic, social, political, cultural, legal, administrative and technological variables on the growth of the forestry sector in India. The analysis indicated that the overall environment does not appear to be conducive for the desired and deserved growth of the sector. The sector has a vast potential contributing to the growth and development of the local communities as well as the national economy. More importantly, it can be used as a vehicle for economic growth with social justice-something that the nation bas aspired to achieve since long. But forestry development in India appears to have lagged behind because of a number of reasons e.g. (i) tbe emphasis on tbe philosophy of sustained yield, (ii) a dualism caused by State ownership and management of forest lands while forest based industries are privately owned and managed, (iii) preference for short-term objectives while allocating development resources (iv) lack of appreciation for the intangible benefits of forestry. This situation is seen as a challenge as well as an opportunity for the professional forester in India.